Adventures in the aid trade : forty years practicing development in forty countries - Holloway, Richard, 1945- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Adventures in the Aid Trade takes us on a fascinating journey through 40 years of work at the coal face of international development. Drawing on his experiences from long periods in the field, the author reflects on what has worked, what has not and why, and considers how these experiences relate to students and practitioners today. Looking beyond high-level policy matters and international relations, this book focuses instead on the author's actual experiences in the field and the inspired local people he encountered. The narrative traces how these people, working through their own organisations, make a difference to the lives of their contemporaries, and learn how they generate the income to do it. Chapters draw on the author's experiences of working with local practitioners from 40 countries across Sub-Saharan Africa, the Caribbean, South, South East, and Central Asia, and the South Pacific. Peppered with lively stories and anecdotes, Adventures in the Aid Trade provides valuable lessons from the shifting aid landscape and reflects on where the industry is likely to go next. Whether you are a current development practitioner, or a student just starting out in your understanding of the development and humanitarian sectors, this book provides an invaluable snapshot of the world of civil society organisations, governance, the voluntary sector, and the lived lives of ordinary people in extraordinary times"--
OCLC-licensed vendor bibliographic record.
Keywords: Economic assistance -- Developing countries; Developing countries -- Economic conditions; SOCIAL SCIENCE / Third World Development